2001
DOI: 10.1289/ehp.0110947
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of airborne Bacillus thuringiensis var. kurstaki during an aerial spray program for gypsy moth eradication.

Abstract: We measured airborne exposures to the biological insecticide Bacillus thuringiensis var. kurstaki (Btk) during an aerial spray program to eradicate gypsy moths on the west coast of Canada. We aimed to determine whether staying indoors during spraying reduced exposures, to determine the rate of temporal decay of airborne concentrations, and to determine whether drift occurred outside the spray zone. During spraying, the average culturable airborne Btk concentration measured outdoors within the spray zone was 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…[27–29] Some agricultural use pesticides are highly persistent and can be found in treated soils and dust even decades after application, indoors [30–32] and in ambient air. [33,34] A California central valley study assessed inhalation risks from airborne agricultural pesticides and concluded that agricultural applications of organophosphates and their oxon products may have substantial volatization and off-field movement.…”
Section: Introductionmentioning
confidence: 99%
“…[27–29] Some agricultural use pesticides are highly persistent and can be found in treated soils and dust even decades after application, indoors [30–32] and in ambient air. [33,34] A California central valley study assessed inhalation risks from airborne agricultural pesticides and concluded that agricultural applications of organophosphates and their oxon products may have substantial volatization and off-field movement.…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft wakes typically sink at 0.3–1.0 m/s [ 32 ], pushing the smaller (40–80 μm) droplets downward into the forest canopy [ 33 ]. Following the dissipation of the aircraft wake, spray droplets are affected by wind, air temperature, humidity, and characteristics of the ground cover [ 34 ], and small droplets may remain in the air column for hours after application [ 35 ]. As a result, active ingredients can be found hundreds of meters from the point of application [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within the context of two spatial dimensions × time much work is largely descriptive. For example, Teschke et al [ 36 ] and Bell et al [ 37 ] use maps at several timepoints, with the maps essentially being descriptive devices. The more complex models are generally Bayesian and use either geostatistical methods or the convolution CAR prior of [ 8 ].…”
Section: Discussionmentioning
confidence: 99%